Pengaruh Tata Kelola Perusahaan Dan Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur Di Indonesia - Arif Zulfahmy; Jeni Susyanti; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of corporate governance and tax planning on earnings management either simultaneously or partially. The method used in this research is multiple linear regression method. The research sample was 35 companies taken by purposive sampling method. In this study using quantitative research. This type of research is explanatory research (explanatory research).The results of this study indicate that corporate governance and tax planning simultaneously have a significant effect on earnings management. And partially corporate governance has no significant effect on earnings management, tax planning partially has a significant effect on earnings management.Keywords: Corporate Governance, Tax Planning, Profit Management